An adolescent with significant emotional and medically unexplained complaints: case report and proposal of an intervention. Issue 1 (December 2015) - Negash, Alemayehu; Abera, Mubarek; Gruber-Frank, Christine; Frank, Reiner
Abstract Background Ethiopia is a country in which child and adolescent mental health needs are often not met. In order to promote capacity building, a Collaborative International Exchange Programme has been established between Jimma University at Jimma, Ethiopia, and Ludwig-Maximilian University in Munich, Germany. The programme focuses on training non-physician health professionals in mental health speciality. One of the courses in the training programme, child psychiatry, involves a child psychiatrist and a children's nurse supporting the management of a patient described in this case report. Its conceptual framework is based on the section "significant emotional and medically unexplained complaints" of the "WHO mental health GAP intervention guide for mental, neurological and substance use disorders in non-specialized health settings". Objective The purpose of this case report is to promote confidence in mental health professionals when managing patients with similar conditions, and to stimulate further evaluation of the conceptual approach in developing countries. Patient The subject of this case report is a 14-year-old adolescent girl admitted to the psychiatric clinic at Jimma University Teaching Hospital. She was admitted for intractable retching, inability to eat, weight loss, and inability to walk. Challenges included the combination of medical and psychiatric symptoms, and the significant impairment of functioning in this adolescent. The first aim in the management of this patient was to guarantee vital functions. In a problem-oriented approach, different domains were addressed to restore nutritional, social, emotional, and motor functions. Treatment consisted of various elements of psychosocial interventions. The patient improved in 2 weeks and the final diagnosis was conversion disorder. Conclusion Psychosocial interventions can be developed in cooperation, and applied in a setting where little child mental health expertise is available. Case-based learning relying on local expertise is suitable in meeting local needs and in developing mental health services for children and adolescents.